Peran KH. Ahmad Dumyati Dalam Keagamaan Di Desa Seribandung Tahun 1960-1996 M - Ramadhan Ramadhan; Fitriah Fitriah (Tanjak: Sejarah dan Peradaban Islam, 2021)
This study describes the role of KH. Ahmad Dumyati in Religious Social Life in Seribandung Village, Ogan Ilir Regency in 1379-1416 H/1960-1996 M. KH. Ahmad Dumyati is the second mudir at the Pondok Pesantren Nurul Islam Seriandung. Apart from a mudir KH. Ahmad Dumyati is a religious figure from Seribandung Village, he is a kiai who is active in preaching using the cawisan method. KH. Ahmad Dumyati is a preacher and is also active in organizational careers, both educational and political organizations. KH. Ahmad Dumyati himself was appointed a member of the DPRD / TK I South Sumatra in 1971.